Posledice kirurškega zdravljenja pri bolnikih z rakom - Brecelj, Erik (Rehabilitacija (Ljubljana), 2008)
During the last decades, survival rates for cancer have increased as a result of earlier detection and combined therapy. That success has led to the need to consider the long-term morbidity associated with the oncologic treatment. After survival, the quality of life has become the second most important parameter in the evaluation of the treatment of patients with cancer.
Keywords: kirurško zdravljenje; kvaliteta življenja; Neoplasms; posledice; Quality of life; rak (medicina); Rehabilitation; Surgery